Pyrolysis-gas chromatography-mass spectrometry analyses of oil-bearing fluid inclusions composition - Yan'e CHEN; Zhirong ZHANG; Paul GREENWOOD (Shiyou shiyan dizhi, 2021)
The molecular compositions of oil-bearing fluid inclusions (FIs) are valuable for the research of oil and gas accumulation; however, due to the very trace amount of materials included, the requirements of commercial instruments cannot be satisfied and thus custom designed instruments were needed for this method, which is difficult to be achieved and the application for the molecular composition of FIs have been limited. In this paper, three samples of oil-bearing FIs were analyzed by pyrolysis-gas chromatography-mass spectrometry (Py-GC-MS) to obtain their hydrocarbon composition. The first sample was a synthetic inclusion prepared by the occlusion of a small amount of crude oil from the Halibut oil field, the second sample was from Australian Jabiru oil field and the third sample was collected from the Tahe oil field in the northwestern China. A diverse range of aliphatic compounds, including n-alkanes, mono-, di- and tricyclic aromatic hydrocarbons and other components have been successively detected from these materials of which, the n-alkanes were monitored up to carbon numbers over C30. Also, the results showed that the method introduced here gave comparable molecular characteristics with data obtained from other traditional methods. The mature degree calculated from Py-GC-MS is very close to that of MCI method. However, it is also notable that the thermal maturity parameters calculated from the results of inclusion analysis were much lower than those of crude oil, indicating modification caused by late-stage alteration to oils in reservoir. As a conventional and easy performed analytical method specially designed for the degradation of macromolecule, the Py-GC-MS demonstrated here is also suitable for the analysis of FIs.